A comparative study on household level energy consumption and related emissions from renewable (biomass) and non-renewable energy sources in Bangladesh. (March 2018) - Baul, T.K.; Datta, D.; Alam, A.
Abstract: In developing countries, securing clean and equal energy access for all is often constrained by lack of understanding of households' energy dependency and influencing factors. This study investigates household-level energy consumption patterns, relevant socioeconomic factors and carbon-emissions from various energy sources. Using a semi-structured questionnaire, we conducted an explorative survey of 189 households in three income groups in a suburban region of Chittagong, Bangladesh. Results suggest that most of the households heavily depend on biomass energy that accounts for 87% of their monthly energy consumption and about two-thirds of energy expenditure. Contrariwise, dependence on non-renewable energy is minimal and accounts for households' 31% monthly energy expenditure. The rich households tend to rely more on electricity, candle, liquid petroleum gas (LPG) while their consumption of the non-renewables is significantly higher than that of medium-income and poor households. Income, education and landholdings of households are positively correlated with expenditure for consuming convenient energy sources such as firewood, electricity and LPG. Firewood, the biomass fuel used most for cooking, is an energy source with the highest carbon emissions—monthly about 192 kg carbon dioxide equivalent per household. Our research findings offer insights to enhance household-level clean energy access in Bangladesh and countries alike. Highlights: Monthly consumptions of biomass are higher than that of non-renewables. Firewood, the biomass used most for cooking, is a source of highest CO2 emissions. The rich households amongst the income groups consume more non-renewable energy. Households' income and education are positively correlated with convenient energy use. Households spend 10% and 4% of their total income for biomass and non-renewables.